Transcriptomic comparison of seeds and silique walls from two rapeseed genotypes with contrasting seed oil content - Guo, Xupeng; Yan, Na; Liu, Linpo; Yin, Xiangzhen; Chen, Yuhong; Zhang, Yanfeng; Wang, Jingqiao; Cao, Guozhi; Fan, Chengming; Hu, Zanmin (Frontiers in Plant Science, 2023)
Light plays considerable roles in storage reserves, and photosynthetically derived sugars are converted mainly into oils in the oilseed. However, the interaction between seeds and silique walls impacting oil biosynthesis is not clear during silique development. In this research, changes in sugar, fatty acid and gene expression during Brassica napus silique development of L192 with high oil content and A260 with low oil content were investigated. In silique development (15, 25 and 35 DAF), silique walls (SWs) contained more hexose than seeds, but seeds contained more sucrose than SWs. The expression of genes related to photosynthesis was inhibited over the period from 15-35 DAF, but they were expressed at much higher levels in SWs than in contemporaneous seeds. The hexose content in the 15 DAF silique of L192 was higher than that of A260, and the sucrose content in the seed of L192 was much higher than that in the seed of A260 only at 25 DAF. Differential gene expression analysis between L192 and A260 showed that the number of upregulated genes relative to photosynthesis in L192 was significantly higher than that in A260 at 25 and 35 DAF in SWs and at both 15 and 35 DAF in the seed. The expression of sugar transporter genes in L192 was higher than that in A260, especially at 35 DAF. The expression of genes related to fatty acid biosynthesis, such as BCCP2s, bZIP67 and LEC1s was higher in L192 than in A260, especially at 35 DAF; meanwhile, genes related to oil body proteins were expressed at much lower levels in L192 than in A260. The genotype with high oil could represent a higher capability of photosynthesis and sugar transportation to seeds in the silique walls, which enhanced the oil accumulation in the seed. Some hub modules, such as ME.turquoise relative to photosynthesis, ME.green relative to embryo development and ME.yellow relative to lipid biosynthesis, were identified and synergistically regulated seed development and oil accumulation. Our results are helpful for understanding the mechanism of oil accumulation of seeds in oilseed rape for seed oil content improvement.